Znaczenie prognozy kryminologiczno-społecznej i warunkowego przedterminowego zwolnienia dla resocjalizacji w orzecznictwie sądów = The significance of socio-criminological forecast and conditional early release for resocialization in judicial practice - Sobański, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents legal aspects of conditional early release, and it focuses on the influence of socio-criminological forecast on probation. If prisoners make substantial progress in their resocialisation in correctional unit, they can be conditionally early released by the court. Further treatment of convicts depends on the course of their social rehabilitation process at large.
Keywords: warunkowe przedterminowe zwolnienie; prognoza kryminologiczno-społeczna; resocjalizacja; conditional early release; socio-criminological forecast; resocialisation; probation